Dehydroabietic acid chemosensitizes drug-resistant acute lymphoblastic leukemia cells by downregulating survivin expression - Li-Li Shen; Wei-Hua Huang; Hui-Jun Zhao; Xue-Wei Yuan (Asian Pacific Journal of Tropical Biomedicine, 2022)
Objective: To explore the mechanism of drug resistance in acute lymphoblastic leukemia and the anti-tumor effect of combination therapy of dehydroabietic acid and vincristine against acute lymphoblastic leukemia cells. Methods: Acute lymphoblastic leukemia cells REH and CCRF- CEM were employed to detect the anti-tumor effect of vincristine and doxorubicin on proliferation and apoptosis using EdU assay, human active caspase-3 Quantikine ELISA kit, and flow cytometry. Vincristine-resistant REH cells (REH-R), survivin knockdown and overexpressing REH cells were established to verify the role of survivin in drug resistance. Additionally, in vitro and in vivo assays were performed to determine the effect of dehydroabietic acid on the cytotoxicity of vincristine. Results: Vincristine and doxorubicin markedly suppressed proliferation and induced apoptosis of REH and CCRF-CEM cells. Survivin expression was upregulated in REH-R cells compared with REH cells. Knockdown of survivin expression obviously restored the sensitivity of REH-R cells to vincristine. Akt phosphorylation was also increased in REH-R cells compared to REH cells. In addition, LY294002, a PI3k/Akt pathway blocker, inhibited survivin expression and enhanced cytotoxicity of vincristine to REH-R cells. Dehydroabietic acid effectively reduced survivin expression in REH-R cells, thereby enhancing the therapeutic effect of vincristine on drug-resistant cells. Survivin overexpression markedly reduced the effect of dehydroabietic acid on enhancing the anti-proliferation and inducing apoptosis effect of vincristine. Moreover, the combination of dehydroabietic acid with vincristine significantly extended the survival rate in a mouse xenograft model of acute lymphoblastic leukemia, compared with vincristine treatment alone. Conclusions: Dehydroabietic acid may be used as a potential candidate for the treatment of acute lymphoblastic leukemia in combination with vincristine.